Two species of Brachyunguis (Hemiptera: Aphididae) new to Iran, and a key to the Iranian species of this genus - Barjadze, Shalva; Özdemir, Işil; Ebrahimi, Ebrahim (Zootaxa, 2022)
Brachyunguis dendrostellerae Kadyrbekov, 2014 and B. monstratus Kadyrbekov, 1999, both living on Diarthron lessertii (Wikstr.) Kit Tan. (Thymelaeaceae), are recorded for Iranian aphid fauna for the first time. The hitherto unknown alate viviparous females of B. dendrostellerae are described, and the little-known apterous viviparous females are redescribed. An identification key for apterous viviparous females of Brachyunguis species known from Iran is provided.